Evaluation of Workplace Online CB-ART Interventions for Reducing Disaster-Related Distress. - Segal-Engelchin, Dorit; Sarid, Orly (Journal of Loss & Trauma, 2026)
Research suggests that the workplace is an effective platform for delivering disaster interventions, highlighting the benefits of implementing early and brief post-disaster interventions both within and outside of workplace settings. This pilot study sought to expand empirical knowledge of a unique brief disaster intervention—the single-session cognitive behavioral and art-based (CB-ART) intervention—by exploring its online use in a workplace setting during wartime conditions. In this single-session intervention, 12 employees sequentially drew three images: their disaster-related stress, their resources, and an integration of these. The aims of the study were to (1) identify the strategies participants employed to mitigate their distress, as evidenced by their drawings and accompanying narratives; (2) assess whether participants experienced a significant reduction of distress levels post-intervention; and (3) explore the resources utilized by participants after the intervention. Results highlight participants' compositional transformations of the stressful image, including changes in size, color, and placement within the integrative drawing, which enabled them to modify its emotional content. Further support for the significance of the CB-ART intervention is evident in the significant decrease in participants' distress levels after the intervention, measured by the Subjective Units of Distress Scale, as well as in the illustrative examples of the resources used several months post-intervention. On a practical level, our study offers a tool that can be easily implemented online during disaster times, ensuring that workplace support remains accessible despite disruptions. Our findings may encourage health policymakers to consider workplace settings as valuable platforms for disaster interventions, thereby conserving resources needed during crises.